Community Infections Linked with Parvovirus B19 Genomic DNA in Wastewater, Texas, USA, 2023–2024 - Alessandro Zulli; Rebecca Y. Linfield; Dorothea Duong; Bridgette Hughes; Alexandria B. Boehm (Emerging Infectious Diseases, 2025)
We assessed concentrations of parvovirus B19 DNA from 2 wastewater treatment plants in a Texas, USA, county with a known outbreak in 2024. Wastewater viral concentrations correlated significantly with clinical cases, demonstrating wastewater’s potential for tracking parvovirus B19 infections. Peaks in wastewater concentrations were aligned with the peak in hydrops fetalis diagnoses.